Solid waste collection optimization objectives, constraints, modeling approaches, and their challenges toward achieving sustainable development goals. (20th December 2020) - Hannan, M.A.; Hossain Lipu, M.S.; Akhtar, Mahmuda; Begum, R.A.; Al Mamun, Md Abdullah; Hussain, Aini; Mia, M.S.; Basri, Hassan
Abstract: Solid waste collection (SWC) has been one of the growing challenges throughout the world due to the development of urbanization and uncontrolled growth of the population. It is a complex process that is expensive and requires the elaborate logistics management and in-depth mathematical computation. Hence, there is an urgent necessity to develop an efficient waste collection process while saving time, fuel, labour, maintenance costs, and carbon emissions. This goal of this is paper is to deliver a comprehensive review of the SWC system concerning solid waste collection objectives, constraints, the different optimization approaches, and models, along with their strengths and weakness. The different types of optimization objectives and constraints on SWC are highlighted towards improving solid waste collection and minimizing the cost. Furthermore, this review has classified the available optimization methods into different categories and technologies to provide a clear understanding for the readers. Besides, future research gaps are identified through the investigation of various key issues and challenges of the existing methods. Moreover, the significant contributions of SWC in connection to sustainable development goals (SDGs) are explained thoroughly. Finally, the review delivers some important proposals that would be beneficial to the researchers and policymakers to design an efficient and robust SWC system toward achieving SDGs. Highlights: A comprehensive review of the optimization methods on SWM and collection. Detailed investigation on SWC objectives, constraints and moels are highlighted. Research gaps are identified based on issues and challenges of the existing methods. S ignificant contributions of SWM related to SDGs are explained thoroughly. This review delivers suggestions to design future robust SWM toward achieving SDGs.